2008
DOI: 10.1144/sp294.8
|View full text |Cite
|
Sign up to set email alerts
|

São Luís Craton and Gurupi Belt (Brazil): possible links with the West African Craton and surrounding Pan-African belts

Abstract: The São Luís Craton and the Palaeoproterozoic basement rocks of the Neoproterozoic Gurupi Belt in northern Brazil are part of an orogen having an early accretionary phase at 2240-2150 Ma and a late collisional phase at 2080 + 20 Ma. Geological, geochronological and isotopic evidence, along with palaeogeographic reconstructions, strongly suggest that these Brazilian terrains were contiguous with the West African Craton in Palaeoproterozoic times, and that this landmass apparently survived subsequent continental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The Paleoproterozoic was a very important crust- forming period of time marked by long-lived granitic magmatism in Africa and South America [29,30] as similar ages on orthogneisses and granitoids have been documented from the Nigerian basement complex, parts of the West African craton, the Zenaga inlier, Morrocco [31], the Borborema Province [32], Gurupi Belt, Brazil [33], Sao Luis craton, Brazil [34], and the Sao Francisco craton, Brazil [35], among others. It has been suggested on the basis of geological and geochronological data that the Amazonian, West African, Sao Francisco, Congo cratons as well as the basements of the Araguaia, Borborema, Nigerian and Cameroon provinces were part of the Atlantica Supercontinent established at the end of the Trans-Amazonian/Eburnean orogenic cycle at ca 2000 Ma [35].…”
Section: Discussionmentioning
confidence: 89%
“…The Paleoproterozoic was a very important crust- forming period of time marked by long-lived granitic magmatism in Africa and South America [29,30] as similar ages on orthogneisses and granitoids have been documented from the Nigerian basement complex, parts of the West African craton, the Zenaga inlier, Morrocco [31], the Borborema Province [32], Gurupi Belt, Brazil [33], Sao Luis craton, Brazil [34], and the Sao Francisco craton, Brazil [35], among others. It has been suggested on the basis of geological and geochronological data that the Amazonian, West African, Sao Francisco, Congo cratons as well as the basements of the Araguaia, Borborema, Nigerian and Cameroon provinces were part of the Atlantica Supercontinent established at the end of the Trans-Amazonian/Eburnean orogenic cycle at ca 2000 Ma [35].…”
Section: Discussionmentioning
confidence: 89%
“…This is due to the early propagation of a Guinea-Liberia rift system into South America (Fig. 15A) and to the presence of the Sao Luis craton (Klein and Moura, 2008) that acted as a rheological lithospheric heterogeneity (Fig. 15B).…”
Section: Rifting and Large-scale Kinematicsmentioning
confidence: 99%
“…(1984). The shape of this cratonic fragment is based on the geophysical interpretation of and is taken from Klein and Moura (2008). Villeneuve (2008) extensively reviewed the orogenic belts on the western side of the West African Craton.…”
Section: Age Of the Amazonian-são Francisco-congo Collision Along Thementioning
confidence: 99%
“…At the southeastern part of the belt, the medium-grade metasedimentary rocks of the Marajupema Formation were found, thrust over the basement rocks. Klein and Moura (2008) suggested that the Neoproterozoic tectonic event was due to a collision between the São Luis…”
Section: The Bassarides Rokelides Araguaia and Gurupi Beltsmentioning
confidence: 99%
See 1 more Smart Citation